Antagonist Activity of Gliocladium sp. Against Fusarium Wilt Fungi in Chili Plant (Capsicum frutescens L.) - Pijoh, Cheryl; Mantiri, Feky Recky; Nio, Song Ai (Universitas Sam Ratulangi, 2025)
Fusarium sp. is a pathogen that causes wilt disease in chili plant (Capsicum frutescens L.), which has a significant impact on crop production. One of the environmentally friendly control strategy is the use of biological agents, such as Gliocladium sp. This study aimed to evaluate the antagonistic ability of Gliocladium sp. to inhibit the growth of Fusarium sp. in vitro. The experiment was conducted using the dual culture method on Potato Dextrose Agar (PDA) medium. Fusarium sp. isolates were obtained from the culture collection of BPPMTPH Kalasey. Observations were carried out of seven days to assess colony growth and calculate the percentage of inhibition. Gliocladium sp. demonstrated the ability to inhibit Fusarium sp. growth, with a maximum inhibition percentage of 51.52% on the seventh day. Gliocladium sp. exhibited rapid growth and dominated the medium, covering the pathogen colony entirely, although no clear inhibition zone was formed. The antagonistic mechanism is presumed to involve competition for space and nutrients, and parasitism. The mechanism of competition was demonstrated by the ability of Gliocladium sp. to grow more rapidly and dominate the PDA medium compared to Fusarium sp. in the dual culture treatment. Parasitism was identified through the coiling of Fusarium sp. hyphae by Gliocladium sp. hyphae, accompanied by morphological abnormalities observed in Fusarium sp. These findings indicate that Gliocladium sp. has potential to be developed as a biological control agent against Fusarium wilt desease in chili plants.